Timing of transcranial direct current stimulation at M1 does not affect motor sequence learning - Hakjoo Kim; Bradley R. King; Willem B. Verwey; John J. Buchanan; David L. Wright (Heliyon, 2024)
Administering anodal transcranial direct current stimulation (tDCS) at the primary motor cortex (M1) at various temporal loci relative to motor training is reported to affect subsequent performance gains. Stimulation administered in conjunction with motor training appears to offer the most robust benefit that emerges during offline epochs. This conclusion is made, however, based on between-experiment comparisons that involved varied methodologies. The present experiment addressed this shortcoming by administering the same 15-minute dose of anodal tDCS at M1 before, during, or after practice of a serial reaction time task (SRTT). It was anticipated that exogenous stimulation during practice with a novel SRTT would facilitate offline gains. Ninety participants were randomly assigned to one of four groups: tDCS before practice, tDCS during practice, tDCS after practice, or no tDCS. Each participant was exposed to 15 min of 2 mA of tDCS and motor training of an eight-element SRTT. The anode was placed at the right M1 with the cathode at the left M1, and the left hand was used to execute the SRTT. Test blocks were administered 1 and 24 h after practice concluded. The results revealed significant offline gain for all conditions at the 1-hour and 24-hour test blocks. Importantly, exposure to anodal tDCS at M1 at any point before, during, or after motor training failed to change the trajectory of skill development as compared to the no-stimulation control condition. These data add to the growing body of evidence questioning the efficacy of a single bout of exogenous stimulation as an adjunct to motor training for fostering skill learning.